Histopatologi Paru-Paru Tikus Putih (Rattus norvegicus B.) Galur Wistar setelah Paparan Asap Rokok Putih - Riyadi, Adhitya Yoga Pradana; Sunarno, Sunarno; Isdadiyanto, Sri (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Cigarettes are tobacco products consumed by burning and inhaling the smoke, while white cigarettes are made from pure tobacco without additional additives, resulting in a distinctive aroma and a relatively lower nicotine content. Continuous exposure to cigarette smoke can increase the risk of respiratory disorders. This study aimed to analyze the effects of white cigarette smoke exposure on changes in lung histopathology of white rats. The study employed a completely randomized design using 24 male white rats weighing 250–300 g, divided into four treatment groups: control, exposure to smoke from one cigarette per day, two cigarettes per day, and three cigarettes per day. The observed parameters included bronchiolar diameter, bronchial diameter, and organ weight as parametric data, as well as lung damage scores as non-parametric data. Parametric data were analyzed using analysis of variance followed by Duncan’s test, while non-parametric data were analyzed using the Kruskal–Wallis test followed by Dunn’s test at a 5% significance level. The results showed that white cigarette smoke exposure had a significant effect on lung damage scores but did not significantly affect bronchiolar diameter, bronchial diameter, or organ weight. It can be concluded that exposure to white cigarette smoke causes lung tissue damage and narrowing of the respiratory tract diameter, which are included in changes in lung organ biometry.